2019
DOI: 10.7759/cureus.6436
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Ectopic Pregnancy in an Accessory Horn of Uterus: A Case Report

Abstract: A unicornuate uterus with an accessory horn is one of the rarest congenital uterine anomalies; hence, the possibility of ectopic pregnancy in the accessory uterine horn is highly uncommon. It poses a significant risk to maternal life, as it is difficult to identify before surgery due to the severe hemoperitoneum in the event of rupture of the ectopic pregnancy. We report a case of a 20-year-old primigravida who presented to the emergency department of Civil Hospital Karachi, with sudden onset of generalized ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Emergency open surgery with multiple blood transfusions is the only option. 14,15 But with advent of better diagnostics, and more women being diagnosed in first trimester scans, medical line of management with surgical removal being done on a later date has become possible. 5 There are no fixed guidelines to manage such ectopics, but like management of other ectopic pregnancy, in early hemodynamically stable pregnancy, intrauterine or intramuscular methotrexate, or intrauterine KCL can be injected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency open surgery with multiple blood transfusions is the only option. 14,15 But with advent of better diagnostics, and more women being diagnosed in first trimester scans, medical line of management with surgical removal being done on a later date has become possible. 5 There are no fixed guidelines to manage such ectopics, but like management of other ectopic pregnancy, in early hemodynamically stable pregnancy, intrauterine or intramuscular methotrexate, or intrauterine KCL can be injected.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier days, or in places where access to health care is difficult, when diagnosis is a problem, women often come with rupture of rudimentary horn with unstable hemodynamic condition. Emergency open surgery with multiple blood transfusions is the only option 14,15 . But with advent of better diagnostics, and more women being diagnosed in first trimester scans, medical line of management with surgical removal being done on a later date has become possible 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The top 10 research priorities for female and unexplained infertility were identified during a consensus development meeting involving 41 participants from 11 countries (Table 1). 1 Anjila Roumia, MD, 1 Samantha Yee, Ph.D, 2 Ari Y. Baratz, MD, 3 Karen B. Glass, MD, 2 Prati Sharma, MD, 2 Clifford Lawrence Librach, MD 2 1 CReATe fertility centre, Toronto, ON, Canada; 2 CReATe Fertility Centre, Toronto, ON, Canada; 3 University of Toronto, Toronto, ON, Canada.…”
Section: E222mentioning
confidence: 99%
“…A rare case of term viable secondary abdominal pregnancy following rupture of a rudimentary horn: a case report. Journal of medical case reports, 3 (1)…”
mentioning
confidence: 99%
See 1 more Smart Citation